Recent advances on polymeric hydrogels as wound dressings - Zheng Pan; Huijun Ye; Decheng Wu (APL Bioengineering, 2021)
Severe hemorrhage is a leading cause of high mortality in critical situations like disaster, accidents, and warfare. The resulting wounds could induce severe physical and psychological trauma to patients and also bring an immense socio-economic burden. Hence, rapid hemostasis and wound healing techniques have become critical initiatives for life-saving treatment. Although traditional methods relying on bandages and gauzes are effective in controlling hemorrhage, they suffer from several limitations: nonbiodegradability, being susceptible to infection, being unsuitable for the irregular wound, secondary tissue damage, and being almost ineffective for wound healing. Owing to the merits of high porosity, good biocompatibility, tunable physicochemical properties, and being beneficial for wound healing, hydrogels with excellent performance have drawn intensive attention and numerous novel effective hydrogel dressings have been widely developed. In this Review, after introducing some commonly used strategies for the synthesis of hydrogels, the most recent progress on polymer-based hydrogels as wound dressings is discussed. Particularly, their hemostasis, antibacterial, and biodegradation properties are introduced. Finally, challenges and future perspectives about the development of hydrogels for wound dressings are outlined.